Differential affection of the visual information sub-streams in a patient with visual agnosia - Lederer, Kirstin; Fimm, Bruno; Munzert, Jorn; Reiser, Mathias; Maurer, Heiko; Binkofski, Ferdinand; Pellicano, Antonello (Frontiers in Psychology, 2025)
IntroductionVisual agnosia is a deficit of object recognition addressed to the damage of the ventral stream (VS). The dorsal stream (DS) is usually intact in these patients, and it can be derived from well-preserved reaching and grasping of visually presented objects. In this study, we presented a new case of a visual agnosic patient (AC) with an extensive lesion of the secondary visual cortex.MethodsWe examined the kinematics of his grasping behavior towards common day-to-day objects compared to a healthy control group. Both colored and color-masked objects were presented, and participants were instructed to grasp-then-name and name-then-grasp them.ResultsThe agnosic deficit was particularly evident when no color information was available to the patient: Although AC was able to recognize most colored objects with marked delay, his recognition of color-masked objects was very poor. Furthermore, the color-masked condition determined larger impairments in kinematic performance relative to the control group.DiscussionResults support the view that spared color processing in the VS allows for partial compensation of deficits. Color information is also processed along the DS, contributing to visuomotor transformations.